Análise do comportamento mecânico de corpos de prova produzidos em impressora 3D com o uso do PLA (ácido poliláctico) - Oliveira, Anderson Ramon Santos Vitorino de (Universidade Federal Rural do Semi-Árido, 2021)
The constant growth in the use of 3D printers is already a reality, so with this equipment, it is possible to create, in a simple and practical way, several types of innovative products capable of impacting different areas of study. Thus, this work seeks to evaluate the mechanical behavior of polylactic acid (PLA), printed on a 3D printer, through experimental mechanical tests, as well as the analysis of these tests through digital image correlation. For this purpose, standardized test specimens in accordance with the ASTM D2990 - 17 standard were built using a 3D printer to carry out tensile and bending tests in a 100kN EMIC DL electromechanical testing machine, which transfers the tension data capture formation for the computer. After that, the digital image correlation method is used, through the MatLAB software, to analyze micro deformations suffered by the material during the test, so that it can be done by comparing these data with the data obtained by the testing machine. Finally, through the analyzes and tests performed, it was possible to obtain various information about the mechanical behavior of PLA, such as the yield limit for traction, bending, its elastic and plastic behavior and material modulus of elasticity.
Keywords: Ácido polilático; PLA; Ensaios mecânicos; Correlação digital de imagens; Polylactic acid; PLA; Mechanical tests; Digital image correlation; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA